Blockchain and IoT Technology Transformation in Indonesian Education - Supriadi, Ajay; Iqbal, Muhammad Faiz; Pratista, Alva Nandana; Sriyono, Diaz Mauludin; Buanasari, Dheaka Jaya (IAIC Bangun Bangsa, 2023)
Every area of life has been touched by technology, and the education industry is no different. Recently, there have been seismic shifts. Teachers and students used a blackboard technique in the traditional classroom teaching-learning process. But this process' characteristics have changed during the last few years. Technology has snuck in and significantly improved it. On the one hand, whereas in conventional classrooms the players were the teachers, the students, and the books, in the modern classroom the players are the teachers, the students, robots, the e-books, the laptops, and the books. With the help of e-lectures and tutorials, the teaching-learning process can now transcend geographical borders in classrooms. For the process, a vast amount of information is easily available. Additionally, the current situation shows a change from